2014
DOI: 10.1590/1678-6997
|View full text |Cite
|
Sign up to set email alerts
|

Fungi infection in honeybee hives in regions affected by Brazilian sac brood

Abstract: The Brazilian Sac Brood is a disease that affects apiaries of Africanized bee hives in Brazil, thereby making them susceptible to high losses. This study investigated the pathogenicity of Africanized bee hives by the entomopathogenic fungi in a Brazilian Sac Brood endemic region. The degree of fungal contamination, presence of mycotoxins in beehive elements, and vulnerability of healthy beehives in environments subjected and not subjected to the disease were investigated. From the contaminating fungal load, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…The presence of these extrolites in honey and pollen samples wasn’t subject of this study; however, if present, they can affect the quality of the honey and pollen. How insects cope with mycotoxins has rarely been investigated (Gliński and Jarosz 2000 ; Traniello et al 2001 ; Keller et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these extrolites in honey and pollen samples wasn’t subject of this study; however, if present, they can affect the quality of the honey and pollen. How insects cope with mycotoxins has rarely been investigated (Gliński and Jarosz 2000 ; Traniello et al 2001 ; Keller et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some bee diseases caused by fungi have not yet been notified by law in Brazil, and the proposed analysis may offer an important signal. Researches conducted by Pacheco et al (2009) and Keller et al (2014) have shown the occurrence of the disease known as Brazilian sac brood (BSB), which is due to some pathogenic fungi and their mycotoxins. These authors recorded unusual frequency of fungal spores and hyphae in honeys, although honeys did not have structure that favors the growth and maintenance of fungi.…”
Section: Resultsmentioning
confidence: 99%
“…However, interestingly and perhaps unknown to many allergic patients and allergists, there are also reports of supplementary bee feeding with food allergen‐loaded mixtures of soybean flour, dried brewer's yeast (containing high levels of residual gluten from brewing processes) and dry skimmed milk with sugar and water 3 . Furthermore, there have been reports of mould contamination within beehives 4 . Both factors suggest a potential for gluten, food and mould allergen protein presence in honey, which could account for some of the reported reactions following honey consumption.…”
Section: Honey Origin Gluten Bos D 5 Bos D 11mentioning
confidence: 99%
“…3 Furthermore, there have been reports of mould contamination within beehives. 4 Both factors suggest a potential for gluten, food and mould allergen protein presence in honey, which could account for some of the reported reactions following honey consumption. As such, the aim of this study was to determine if commercially available honey contained undeclared gluten and/or food or mould allergens, and at levels which could present a risk to individuals with hypersensitivities.…”
mentioning
confidence: 99%